Circulating Tumor Cells, Circulating Tumor DNA and Other Blood-based Prognostic Scores in Pancreatic Ductal Adenocarcinoma - Mini-Review - Liberko, Marian; Kolostova, Katarina; Szabo, Arpad; Gurlich, Robert; Oliverius, Martin; Soumarova, Renata (In vivo (Athens, Greece), 2021)
Pancreatic ductal adenocarcinoma represents a disease with increasing incidence. Its prognosis is the worst among all malignancies despite the aggressive combined multimodal treatment across all stages. In metastatic disease, median survival is approximatelly one year. The mainstay of treatment is chemotherapy (neo/adjuvant, palliative) and in selected subgroups of patients even radiotherapy. Nevertheless, nowadays there are very few prognostic and/or predictive biomarkers available that can be used to identify and better stratify patients based on risk to tailored treatment. Potentially, promising areas of research are circulating tumor cells and circulating tumor DNA, which can be easily obtained from peripheral blood - so called liquid biopsy. They may serve as a tool to assess response to applied treatment, and to detect the emergence of treatment-resistant clones or early disease relapse. Moreover, their study may allow identification of potentially tumor-specific alterations, which may serve as target structures for targeted (tailored) therapy. Alternatively, different prognostic indexes/scores calculated by analysis of selected parameters of blood and/or biochemistry can be used to better stratify patients based on risk and better predict prognosis. The aim of this mini-review is to provide a basic overview of the current state of the art in this area and its potential significance for clinical practice.
Keywords: Circulating Tumor DNA; duktální karcinom slinivky břišní; liquid biopsy; circulating tumor DNA (ctDNA); Carcinoma, Pancreatic Ductal; nádory slinivky břišní; Humans; review; Biomarkers, Tumor; biomarkers; Neoplastic Cells, Circulating; lidé; Pancreatic carcinoma; cirkulující nádorová DNA; nádorové biomarkery; Pancreatic Neoplasms; circulating tumor cells (CTC); prognóza; nádorové cirkulující buňky; lokální recidiva nádoru; prognostic index/score; Neoplasm Recurrence, Local; Prognosis